KC 1.1: Cultural Heritage and Climate Change: Exploring the Impacts and Issues - Brabec, Elizabeth; Potts, Andrew; Polanco, Julianne (ScholarWorks@UMass Amherst, 2019)
As noted at the 2017 ICOMOS Assembly in Delhi, cultural heritage is both under threat from climate change, and an asset in our attempts to adapt to and mitigate its impacts. The Paris Agreement emphasizes the need for urgency about climate change; cultural heritage can play a central role in this effort. For example, iconic sites at risk from storms, coastal erosion, wildfires or permafrost thaw can alert public to the very real impacts and costs of climate change. World Heritage Sites (WHS) around the world play a key role in alerting the public to the impacts of local climate change because they are highly visible, and are acknowledged as being important to national, regional and local heritage. As such, broad publicity about impacts and continuing losses such as the news coverage of the sea-level rise at Rapa Nui and Skara Brae and the degradation of the Cedars of Lebanon illustrate the value of both the iconic sites, their resources, and the wide media coverage they can project. Loss and damage due to climate change also includes the impacts on large landscapes and their associated communities. The loss of cultural heritage in these landscapes runs the gamut from intangible heritage such as folk tales, to immoveable cultural heritage, to the lifeways of cultures that have developed over centuries and millennia. Placing those impacts into a broader context is the role, and the goal, of the CCHWG Working Group. This session will address ongoing work by the Climate Change and Heritage Working Group (CCHWG) of ICOMOS that explores the nexus between climate change and heritage. Heritage interacts with climate change through a spectrum of impacts from the physical degradation of standing structures and site ecosystems, to the role that cultural heritage plays in the resilience of communities and their ontological security. Although the focus of the session will be on the impacts of climate change on rural landscapes, the discussion will cover the broad range of the work of the committee. Attached to this abstract is the full report of the Working Group, delivered to the UNESCO World Heritage Committee (WHC) on June 3, 2019 at the 43rd Meeting of the WHC in Baku, Azerbaijan. The audience will be asked to engage with the report to identify publications and case study examples that should be incorporated into the next steps of the work of the CCHWG.